Direct Tuning Phase-Shift Angle In Dab Dc-Dc Converter Using Moth Flame Optimization (Mfo) Algorithm - Lo, Norman Kun King (2022)
The world is currently experiencing a global energy crisis due to the limited natural energy resources that are used to power industrial society, where as demand increases, the available resources are being depleted. The evolution of renewable energy able to overcome this energy crisis. DC-DC converter is one of the vital components used in the renewable energy system as power conversion tools. However, most of the existing DCDC converter has unidirectional power flow which have limitations in term of energy management efficiency due to one way power flow. Besides, the non-isolated bidirectional power flow has restrictions in high voltage conversion gain, safety and power quality. Therefore, a 100 kW isolated bidirectional Dual Active Bridge (DAB) DC-DC converter with single phase shift (SPS) modulation have been developed using MATLAB/Simulink software. Apart from that, the tuning method of phase-shift angle variable in DAB plays the important role to produce the desired output. Since the conventional tuning has a couple of downsides, mainly related to the time-consuming and inconsistence accuracy, the auto-tuning phase shift angle using Moth Flame Optimization (MFO) algorithm in DAB is proposed in this project. The proposed method is tested in terms of accuracy, efficiency and convergence speed for various load system which is 100 kW, 75 kW and 50 kW under various reference voltage. The results from the research depicts that the DAB system with 100 kW, 75kW and 50 kW respectively has the best convergence speed, highest efficiency and highest accuracy with lowest ripple. With aforementioned results, the MFO algorithm have well-functioning in DAB system.